Improving physical condition of badminton athletes aged 10-12 through circuit body weight training - Wahyu Eko Widiyanto; Heny Setyawati; Mohammad Furqon Hidayatullah; Donny Wira Yudha Kusuma; Taufiq Hidayah; Hermawan Pamot Raharjo; Muhamad Ichsan Sabillah; Yovhandra Ockta (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and Objective: This study investigates the effect of the circuit bodyweight training method on improving physical fitness parameters such as muscle power, cardiovascular endurance, and agility. The goal is to assess how this specific training regimen influences the physical performance of badminton athletes. Methodology: An experimental design with a one-group pre-test and post-test was utilized for this research. A sample of 40 participants, selected through random sampling, underwent assessments to measure leg muscle power (vertical jump), arm muscle power (medicine ball put), cardiovascular endurance (yo-yo test), and agility (pedicure test). The data analysis was conducted using an independent sample t-test followed by a paired sample t-test to determine significant differences in physical performance. Results: The findings revealed a significant improvement in all measured physical parameters post-training, with a p-value of less than 0.05. The average leg muscle power increased from 129.20 kg/sec in the pre-test to 189.60 kg/sec in the post-test, showing a difference of 60.4 kg/sec. The arm muscle power improved from an average of 259.20 cm in the pre-test to 406.00 cm in the post-test, with a difference of 146.8 cm. Cardiovascular endurance increased from an average of 11.7 in the pre-test to 13.2 in the post-test, showing a difference of 1.5. Lastly, agility improved from an average of 29.00/s in the pre-test to 26.10/s in the post-test, with a difference of 3.00/s. Conclusion: Circuit bodyweight training significantly enhanced muscle power, cardiovascular endurance, and agility in badminton athletes. These results indicate the effectiveness of this training method in improving physical condition.